Predação e dispersão de sementes de cutieiras (Joannesia princeps) por cutias (Dasyprocta azarae) na Mata Atlântica - Fernanda Cristina Souza (2017)
The increase in the abundance of conspecific trees may have a negative effect on the performance of plant populations, increasing mortality rates mainly in the early stages of development (seeds and seedlings). However, with the increase of fruit and tree abundance, there may be a higher seed survival and lower dispersal effectiveness due to satiation of predators and seed disperser. We investigated the effects of the abundance of trees and endocarps and the mass of seeds in the removal and fate of cutieira seeds (Joannesia princeps). We tested the following hypotheses: 1) the predation and dispersion of cutieiras seeds will be affected by the availability of trees and endocarps and 2) seed size will influence removal distance. To test these hypotheses, 493 cutie seeds were weighed, tied in spools and distributed in 15 quadrants (sampling units). We also installed camera-traps to identify which species of mammals interacted with cutieira seeds and to estimate visit rates. After 40 days, we found a higher proportion of predated seeds than those dispersed or buried, especially in areas with low tree abundance. However, abundance of trees and endocarps did not influence dispersion. In addition, the removal distances increase of 0.8 meters for each addition by one (1) gram in the mass of the removed seeds. However, abundance of trees and endocarps did not influence dispersion. Agoutis were the only visitors that manipulated and removed the seeds. However, the rate of visits by agoutis showed no relationship with abundance of trees and endocarps. Our results indicate that only seed predation is influenced by the abundance of trees, suggesting that the decrease of seed predation in sites with greater tree abundance can be explained by the satiation of seed predators. In addition, seed mass was more important in predicting the distance the seeds were removed than the availability of trees and endocarps.